2010
DOI: 10.1016/j.alcohol.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the T-ACE in pregnancy in predicting child outcome and risk drinking

Abstract: Preventing Fetal Alcohol Spectrum Disorders (FASDs) requires detection of in-pregnancy maternal risk drinking. The widely used T-ACE screen has been applied in various ways although the impact of those different uses on effectiveness is uncertain. We examined relations among different T-ACE scoring criteria, maternal drinking and child outcome. Self-reported across-pregnancy maternal drinking was assessed in 75 African-American women. The different T-ACE criteria used varied the level of drinking that defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 61 publications
0
24
0
6
Order By: Relevance
“…Our findings, based on low prenatal alcohol exposure, may be in line with this. Several studies have shown that T-ACE is effective in predicting prenatal alcohol consumption, but to the best of our knowledge, only one study has examined whether T-ACE also further predicts toddler outcomes, in that case neurobehavioral deficits (lower IQ) among children of a small sample of African–American women of lower socioeconomic status [39]. We are not aware of other studies that have controlled for the effect of prenatal alcohol exposure on psychosocial outcomes in very young children of risk drinking mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings, based on low prenatal alcohol exposure, may be in line with this. Several studies have shown that T-ACE is effective in predicting prenatal alcohol consumption, but to the best of our knowledge, only one study has examined whether T-ACE also further predicts toddler outcomes, in that case neurobehavioral deficits (lower IQ) among children of a small sample of African–American women of lower socioeconomic status [39]. We are not aware of other studies that have controlled for the effect of prenatal alcohol exposure on psychosocial outcomes in very young children of risk drinking mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Affirmative responses on the A, C and E items were given one point each. A total score ≥3 was used as cut-off point for risk drinking, which has been shown to give good sensitivity and specificity [38, 39]. …”
Section: Methodsmentioning
confidence: 99%
“…We, and others, have effectively used these measures of alcohol use to examine prenatal alcohol-related outcomes (e.g., Beblo et al, 2005; Burden et al, 2005; Jacobson et al, 1994; 1998; 2002; Nordstrom-Bailey et al, 2004). In addition, at the first antenatal visit we assessed problems associated with drinking with the 25-item Michigan Alcoholism Screening Test (MAST; Selzer, 1971), the CAGE screen (Ewing, 1984), and the 4-item T-ACE (or TACER-3) screen (Sokol et al, 1989; Chiodo et al, 2010). The T-ACE/TACER-3 screen includes a question about “tolerance” – the “T” in “T-ACE/TACER-3” – asking how many drinks it takes to feel high.…”
Section: Methodsmentioning
confidence: 99%
“…; AADDXP ≥ 2.5 oz. ; MAST ≥ 5; CAGE ≥ 2; T-ACE ≥ 3 (i.e., the TACER-3 cut-point; Chiodo et al, 2010). With the exception of the T-ACE, all cut-points are based on standard definitions of “at-risk drinking” (cf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation